2006
DOI: 10.1021/bi0518848
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl−Heme Structures of Bacillus subtilis Nitric Oxide Synthase Have Implications for Understanding Substrate Oxidation,

Abstract: The crystal structures of nitrosyl-heme complexes of a prokaryotic nitric oxide synthase (NOS) from Bacillus subtilis (bsNOS) reveal changes in active-site hydrogen bonding in the presence of the intermediate N(omega)-hydroxy-l-arginine (NOHA) compared to the substrate l-arginine (l-Arg). Correlating with a Val-to-Ile residue substitution in the bsNOS heme pocket, the Fe(II)-NO complex with both l-Arg and NOHA is more bent than the Fe(II)-NO, l-Arg complex of mammalian eNOS [Li, H., Raman, C. S., Martasek, P.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
96
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 65 publications
14
96
2
Order By: Relevance
“…The second step, NOHA 3 citrulline ϩ NO, is supposed to involve the direct reaction of the (hydro)peroxo species on the NOHA hydroxyguanidinium moiety, followed by the rearrangement of the resulting tetrahedral complex and the release of citrulline and NO (26,29). These models are supported by crystallographic, spectroscopic, and cryogenic experimental evidences (39,69,80,83,87), but recently serious questions have been raised (30,32). In the absence of the definitive isolation, characterization, and identification of key reaction intermediates, an unequivocal NOS mechanism cannot be advanced and therefore several alternative mechanisms have been proposed for each catalytic step.…”
Section: Various Causes For the Changes In Fementioning
confidence: 80%
See 2 more Smart Citations
“…The second step, NOHA 3 citrulline ϩ NO, is supposed to involve the direct reaction of the (hydro)peroxo species on the NOHA hydroxyguanidinium moiety, followed by the rearrangement of the resulting tetrahedral complex and the release of citrulline and NO (26,29). These models are supported by crystallographic, spectroscopic, and cryogenic experimental evidences (39,69,80,83,87), but recently serious questions have been raised (30,32). In the absence of the definitive isolation, characterization, and identification of key reaction intermediates, an unequivocal NOS mechanism cannot be advanced and therefore several alternative mechanisms have been proposed for each catalytic step.…”
Section: Various Causes For the Changes In Fementioning
confidence: 80%
“…Structural Model of Interaction between Fe II -CO and NOS Substrate-The crystallographic structures of NOS-hemeFe II -CO (39) and ferrous heme-nitric oxide complex (39,83), in the presence of L-Arg and NOHA, suggest the existence of an H-bond between the L-Arg-guanidinium and the distal ligand (39,83). Additionally, in the presence of L-Arg, all crystallographic structures reveal the presence of a structural water molecule involved in H-bonding interactions with both the ligand (CO or NO) and the guanidinium moiety of L-Arg (Fig.…”
Section: Various Causes For the Changes In Fementioning
confidence: 99%
See 1 more Smart Citation
“…The resonance Raman fingerprints of numerous saNOS (39 -41) and bsNOS (42,43) complexes reveal no significant differences in the heme distal environment of bacNOSs and mNOSs (44 -46). Some subtle differences have been observed between the x-ray structures of Fe II NO complexes of bsNOS (47) and neuronal NOS (nNOS) (48,49) in the presence of NOHA and L-Arg, but they should not significantly affect the proton transfer processes. In fact, the variability of the heme distal structure is greater within mNOSs than between bacNOSs and mNOSs.…”
mentioning
confidence: 99%
“…However, NO could react with the pterin radical if the process becomes uncoupled or at high NO concentrations, as may occur during inflammatory responses. Also, NOS enzymes have been shown to sequester NO at non-heme sites near the active site (57,58), which would then be available for reaction with a subsequent pterin radical. Moreover, Schmidt and co-workers (59) showed that NOS catalysis leads to H 4 B loss or modification that is distinct from oxidation and dependent on a NOS-derived reactive nitrogen species.…”
Section: How Might N-no-h 4 B Form During Catalysis? N-no-pterinmentioning
confidence: 99%